Vertical damping of gravity waves evaluated from ACS-TGO solar occultation measurements on Mars - Starichenko, Ekaterina D.; Medvedev, Alexander S.; Belyaev, Denis A.; Fedorova, Anna A.; Trokhimovskiy, Alexander; Hartogh, Paul; Montmessin, Franck; Korablev, Oleg I. (Frontiers in Astronomy and Space Sciences, 2025)
Amplitudes of gravity waves generated in the lower and denser atmospheric layers grow exponentially with height as they propagate to the upper and thinner atmosphere, where they are reduced by various processes. Their vertical decay is accompanied by a transfer of wave momentum and energy to the ambient flow, which represents a significant force in the upper atmosphere. Constraining the vertical damping and elucidating the related mechanisms are crucial for understanding the dynamics. Previous observations of gravity waves in the Martian thermosphere by different instruments provided evidence that amplitudes of relative temperature disturbances are inversely proportional to the mean temperature. This suggests that wave amplitudes may be limited by convective instabilities. However, this anticorrelation was not observed at all heights or in all measurements, sparking a discussion about the dominant mechanisms of wave damping. Using vertical temperature profiles collected by the Atmospheric Chemistry Suite instrument on board Trace Gas Orbiter over more than 6 years, we examined the statistical behavior of wave amplitudes and their vertical damping rates. We found a weak anticorrelation near the mesopause (∼90–140 km), suggesting the presence of convective instability and molecular diffusion mechanisms, but no robust correlations elsewhere. Instead, we found an unexpectedly persistent anticorrelation between the vertical decay rates and ambient temperature at all heights. We demonstrated that above approximately 80 km, wave breaking and/or saturation could be consistent with the convective instability mechanism, but the reason for this behavior at lower altitudes remains unclear.